2018
DOI: 10.4102/sajp.v74i1.400
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of disability policy framework in Namibia: A qualitative study

Abstract: BackgroundThis study explores some of the experiences of national programme managers, heads of national organisations of persons with disabilities (OPDs) and persons with disabilities in the implementation of the disability policies and legal framework in Namibia.MethodIn-depth interviews were conducted with multiple key stakeholders mentioned above. Interviews were digitally recorded and transcribed verbatim. The Community Based Rehabilitation (CBR) matrix (health, education, livelihood, social and empowermen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…A review of policies and legislations in Namibia (Shumba & Moodley, 2018a) identified CBR as underpinning key strategy for delivery of disability and rehabilitation services in the country. Shumba and Moodley (2018b) also confirmed the need to explore the experiences of persons with disabilities in CBR programmes using appropriate qualitative evaluation tools. A scoping review established that Photovoice has the potential to be utilised as a qualitative evaluation tool for effectively eliciting the experiences of persons with disabilities on a CBR programme (Shumba & Moodley, 2018c).…”
Section: Introductionmentioning
confidence: 62%
“…A review of policies and legislations in Namibia (Shumba & Moodley, 2018a) identified CBR as underpinning key strategy for delivery of disability and rehabilitation services in the country. Shumba and Moodley (2018b) also confirmed the need to explore the experiences of persons with disabilities in CBR programmes using appropriate qualitative evaluation tools. A scoping review established that Photovoice has the potential to be utilised as a qualitative evaluation tool for effectively eliciting the experiences of persons with disabilities on a CBR programme (Shumba & Moodley, 2018c).…”
Section: Introductionmentioning
confidence: 62%
“…The study revealed that physical accessibility remains poor despite the advocacy initiatives of CBR volunteers at both sites. The lack of physical accessibility can be attributed to a lack of legislation on physical accessibility in Namibia [5].…”
Section: (4) Socialmentioning
confidence: 99%
“…(3) Able to use a camera and describe his/her photographs, (4) Involvement in the CBR program for at least one year, (5) Have basic advocacy skills to be able to engage in dialogue that can influence policy and decision-making, (6) Be able to read and speak basic English, (7) Must be willing and interested in participating in the project for one month, (8) Must be willing to share their experiences with participant group members and eventually the public.…”
Section: Inclusion Criteria For Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insights into experiences and understandings of those who are ‘exposed’ to CBR can best be obtained through qualitative methods. Recently, Shumba and Moodley ( 2017a ) in their assessment of the implementation of the CBR disability programmes identified the need for a qualitative evaluation tool that can effectively elicit the experiences of persons with disabilities on the CBR Programme.…”
Section: Introductionmentioning
confidence: 99%